(untitled) (Italian Journal of Public Health, 2011)
Background: Studying medicine consumption is a significant parameter in the estimation of the health care system of a country. This study evaluates the amount of medicine consumption in the mega cities of Iran and indentifies individual factors that influence this consumption. Methods: In this study, a cross-sectional survey of public medicine consumption was directed at random samples that counted 628 persons of fifteen years and older in several public places in the mega cities of Iran. The data were collected through questionnaires administered at the public vaccination department of the Pasteur institute of Iran in Tehran, and in other public places in Esfahan. A multiple regression model was utilized to analyze individual information. Results: Our results showed that 59.4% of the respondents were current medicine consumers. Women used medicines less frequently. The rates of medicine consumption among the surveyed population, for daily and weekly-monthly consumption, were 21.8% and 37.6% respectively. In Iran, it emerged that 52.4% of the respondents obtained their medicines, such as acetaminophen antibiotics, and pain-killers, without a prescription. Conclusions: the study clearly showed that more than 53% of the medicine consuming persons undertake self-treatment. Three factors gender, age and income level are the main factors influencing medicines consumed without physicians’ prescription in the mega cities of Iran.